Granite exploration by using resistivity and induced polarization imaging in western granite belt, Pendang, Kedah, Malaysia - Sarbani, Daud; Mohd Fakhrurrazi, Ishak; Ismi, P.I.; Nurmunira, Muhammad; Suriati, Ghazali (Springer Nature, 2025)
A resistivity survey has been conducted in Mukim Padang Peliang, Pendang, Kedah, Malaysia, to assess the granite rock reserve for quarry exploitation. The study area is located along the S-type western granite belt. An electrical resistivity imaging (ERI) with the induced polarization (IP) method together with 2-dimensional (2D) and 3-dimensional (3D) voxel resistivity model analysis was generated in order to attain the anomaly reading related to the granite body in the area. Several software used in data processing are Res2Dinv, SketchUp, and Voxler. Terrameter model LS2, cables, electrodes, cables, connectors, and battery were used as the measurement tools. Five Survey lines were conducted throughout the study area for 400 m each with 5 m inner and 10 m outer spacing using the Wenner-Schlumberger protocol. A comparison of the resistivity value and the induced polarization (IP) led to a better interpretation of the data. 3D modelling of the resistivity has resulted in better presentation, thus relating the data from each survey line into one whole picture. It could be depicted that the orientation of the granite body is distributed in the NW – SE direction. The granite reserve is estimated to be 282.7 million metric tons. The result shows that induced polarization (IP) value is needed to complement the obtained resistivity data, and the 3D model is crucial for finding the interrelationship between all survey lines.